Efecto de la composición del gas de protección en el proceso gmaw sobre los parámetros geométricos en la soldadura de un acero inoxidable austenítico - León Castañeda, Breynner Orlando (2019)
In the present work of investigation has studied the effect of the composition of the gas of protection in the process of welding by arc using gas of protection, GMAW on the geometric parameters in the welding of a stainless steel austenitico AISI 304. Compositions have been evaluated, from 100% CO2, 20% CO2 - 80% Ar and 98% Ar - 2% CO2. as protection gas, in the GMAW welding process, with 4 repetitions per experimental run, making a total of twelve test specimens, the other parameters of the welding process have remained constant. The statistical results show that there is a significant effect of the composition of the protective gas on the geometric faces of the weld bead, such as the cord width and reinforcement area, but not in the dilution. in the welding of AISI 304 steel. It is concluded that the best cord shape characterized by low reinforcement and greater cord width (associated with low wetting angles and high melting angles) together with high penetration and dilution, was obtained with the mixture 98% -2% CO2, in the GMAW arc welding for stainless steels AISI 304.